2016
DOI: 10.1016/j.envres.2016.09.014
|View full text |Cite|
|
Sign up to set email alerts
|

Road traffic noise, blood pressure and heart rate: Pooled analyses of harmonized data from 88,336 participants

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 41 publications
2
21
0
5
Order By: Relevance
“…First, our results suggest that, where both noise and air pollution are independently associated with an acute cardiovascular outcome, neither pollutant completely explains the effect of the other. These findings corroborate results from several previous studies of concurrent exposure to traffic noise and air pollution on cardiovascular outcomes including prevalent hypertension and blood pressure 16 18 , heart rate 17 , incident myocardial infarction 19 , hospital readmission for myocardial infarction 20 , all-cause mortality 20 , heart failure 7 , myocardial infarction mortality 21 and CHD mortality 8 . These studies and others examining correlations between traffic noise and air pollution 22 , 23 were the first to suggest that noise may confound traffic-related health effects in epidemiologic studies of air pollution, and we assessed this potential bias more precisely by using personal exposure measures.…”
Section: Discussionsupporting
confidence: 90%
“…First, our results suggest that, where both noise and air pollution are independently associated with an acute cardiovascular outcome, neither pollutant completely explains the effect of the other. These findings corroborate results from several previous studies of concurrent exposure to traffic noise and air pollution on cardiovascular outcomes including prevalent hypertension and blood pressure 16 18 , heart rate 17 , incident myocardial infarction 19 , hospital readmission for myocardial infarction 20 , all-cause mortality 20 , heart failure 7 , myocardial infarction mortality 21 and CHD mortality 8 . These studies and others examining correlations between traffic noise and air pollution 22 , 23 were the first to suggest that noise may confound traffic-related health effects in epidemiologic studies of air pollution, and we assessed this potential bias more precisely by using personal exposure measures.…”
Section: Discussionsupporting
confidence: 90%
“…Further, there are many ways in which physical environments can obscure information needed for safety, including distortion of information, for example by darkness, dense fog, or loud noise. Continuous noise such as road traffic noise leads to chronic physiological stress activity [ 167 , 168 , 169 ], also during sleep [ 167 ], and increased risks for cardiovascular disease [ 170 , 171 ]. Noise has often been used in stress experiments, and we take it for granted that loud, sustained noise can be used as a stressor.…”
Section: Compromised Domains: Prolonged Stress Responses Without Smentioning
confidence: 99%
“…This is also in line with the literature. In their cohort study, Sørensen et al found that in the subsample of people with prior diagno- 42 . All these results are most likely due to exposure misclassifi cation or other methodological limitations.…”
Section: Findings On Noise and Blood Pressurementioning
confidence: 99%